Burnout syndrome in Medical students: An integrative literature review (Research, Society and Development, 2024)
The aim of this study was to understand how burnout syndrome affects medical students. The integrative literature review was prepared according to the recommendations of the Preferred Reporting Items for Systematic reviews and Meta-Analysis guideline. Database searches were performed using the search strategies “(medical students[Title]) AND (burnout[Title])” in PubMed and “(ti:(medical students)) AND (ti:(Burnout))” in LILACS and SciELO. The inclusion criteria considered were the availability of the free full text, language being English or Portuguese, publication made between January 2014 and July 2024, and study population consisting only of medical students. The following data were extracted from each included article: authorship, year, country, objectives, design, main results and limitations. The scientific literature demonstrated great heterogeneity in the prevalence rates of burnout syndrome in medical students, reaching 17% in Brazilian studies. High-risk factors for burnout syndrome among medical students were chronic stress, female gender, age under 25, being in the first or last year of undergraduate studies, empathic concern, lack of social support, low levels of physical activity, and sleep disorders. The most commonly used strategies for coping with stress were seeking support from friends or family, practicing physical exercise and relaxing activities, which act as protective factors for burnout, as well as empathy, male gender, advanced age, and academic engagement.